Elastic properties of 2D ultrathin tungsten nitride crystals grown by chemical vapor deposition - Wang, Hong (2020)
3D transition metal nitrides are well recognized for their good electrical conductivity, superior mechanical properties, and high chemical stability. Recently, 2D transition metal nitrides have been successfully prepared in the form of nanosheets and show potential application in energy storage. However, the synthesis of highly crystalline and well-shaped 2D nitrides layers is still in demand for the investigation of their intrinsic physical properties. The present paper reports the growth of ultrathin tungsten nitride crystals on SiO2/Si substrates by a salt-assisted chemical vapor deposition method. High-resolution transmission microscopy confirms the as-grown samples are highly crystalline WN. The stiffness of ultrathin WN is investigated by atomic force microscopy–based nanoindentation with the film suspended on circular holes. The 3D Young's modulus of few-layer (4.5 nm thick or more) WN is determined to be 3.9 × 102 ± 1.6 × 102 GPa, which is comparable with the best experimental reported values in the 2D family except graphene and hexagonal boron nitride. The synthesis approach presented in this paper offers the possibilities of producing and utilizing other highly crystalline 2D transition-metal nitride crystals.